Potential of pine needles for PLA‐based composites. Issue 4 (23rd May 2016) - Sinha, Priyasheel; Mathur, Smita; Sharma, Pradeep; Kumar, Vijai
Abstract : The article describes the mechanical properties of biodegradable composites. The composites were made using biodegradable plastics like polylactic acid reinforced with Pinus roxburghii needles. The composites were characterized by their tensile strength, flexural strength, Rockwell hardness, thermal stability, and FTIR analysis as well as morphological and water absorption behavior. The composites possessed high tensile and flexural strength on addition of 8.77% fibers. The tensile and flexural strength increased 1.7 and 3.5 times, respectively, in comparison to virgin PLA. Biodegradation studies revealed that the composites have the capability to degrade in the natural environment. These results reveal that pine needles can be prospective candidates for use in natural fiber‐reinforced polymer composites. POLYM. COMPOS., 39:1339–1349, 2018. © 2016 Society of Plastics Engineers